Creep properties and analysis of creep rupture data of 2.25Cr-1Mo-0.3V steels. Issue 1 (31st December 2022) - Sawada, Kota; Taniuchi, Yasushi; Sekido, Kaoru; Nojima, Takehiro; Kimura, Kazuhiro
ABSTRACT: Tensile properties and creep rupture data were obtained for four heats of 2.25Cr-1Mo-0.3 V steels used for high-temperature and high-pressure hydrotreatment reactor vessels. Tensile tests at room temperature to 650°C were performed in accordance with JIS G 0567. Creep tests at 450 to 600°C were conducted in accordance with JIS Z 2271. Large heat-to-heat variations of tensile and creep rupture data were found with the different heat treatment conditions. However, no large difference in creep rupture ductility was observed among the heats. Regression analysis was applied to the tensile test data of each heat because of the large heat-to-heat variations. The creep rupture data of heats VdA and VdB were separately fitted to the regression equation of logarithmic stress using the time-temperature parameters of Larson–Miller, Orr–Sherby–Dorn and Manson–Haferd to estimate the 100, 000 h creep rupture strength. The appropriate time-temperature parameter and degree of regression equation were selected based on the fitting accuracy and simplicity of regression equation. The value of 67% of the 100, 000 h creep rupture strength was compared with the current allowable stress specified in codes and standards. Graphical abstract: uf0001